On Using Blindness as Metaphor and Difficult Questions: A Response to Ben-Moshe - Deborah J. Gallagher (Disability Studies Quarterly, 2006)
In response to Ben-Moshe's highly engaging examination of Saramago's Blindness and the novel's use of disability as metaphor, I explore the possibility that this novel serves primarily as an indictment of the cultural imperialism of sightedness. Although the novel can certainly be read as an ableist text, I suggest that it might also serve to expose the creation of blindness as a disability through structures of power and domination.
Keywords: Disability Studies; Literature; Blindness